2000
DOI: 10.1016/s0378-5173(00)00348-3
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes encapsulating polymeric chitosan based vesicles — a vesicle in vesicle system for drug delivery

Abstract: Drug delivery systems comprising vesicles prepared from one amphiphile encapsulating vesicles prepared from a second amphiphile have not been prepared previously due to a tendency of the bilayer components of the different vesicles to mix during preparation. Recently we have developed polymeric vesicles using the new polymer-palmitoyl glycol chitosan and cholesterol in a 2:1 weight ratio. These polymeric vesicles have now been encapsulated within egg phosphatidylcholine (egg PC), cholesterol (2:1 weight ratio)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…18 An early example for a multicompartment vesicle showed as well the inverse configuration by encapsulating polymersomes inside a bigger liposome without providing any specific functionality. 157 In contrast, polymersomes were introduced very recently as subcompartments into giant plasma membrane vesicles (GPMVs) to form molecular factories. 142 GPMVs are giant vesicles directly isolated from cells.…”
Section: Biohybrid Multicompartment Polymeric Vesiclesmentioning
confidence: 99%
“…18 An early example for a multicompartment vesicle showed as well the inverse configuration by encapsulating polymersomes inside a bigger liposome without providing any specific functionality. 157 In contrast, polymersomes were introduced very recently as subcompartments into giant plasma membrane vesicles (GPMVs) to form molecular factories. 142 GPMVs are giant vesicles directly isolated from cells.…”
Section: Biohybrid Multicompartment Polymeric Vesiclesmentioning
confidence: 99%
“…Polymeric vesicles show increased retention of dissolved solutes (14) and an increased resistance to solubilization by alcohol (18) or bile salts (9). Additionally, polymeric vesicles prepared from palmitoyl glycol chitosan have recently been encapsulated within phosphatidylcholine liposomes and show a reduced degree of lipid mixing with these liposomes (19).…”
Section: Introductionmentioning
confidence: 99%
“…By combining chitosan and liposomal characteristics, specific, prolonged, and controlled release can be achieved [5 -7]. A solid polymeric vesicle, namely palmitoyl glycol chitosan, was entrapped within a liposomal formulation to control the release profiles of a model compound [8]. A small degree of mixing of the lipids occurred upon hydration of the lipid/surfactant film, resulting in a vesicle formulation instead of a vesicle in vesicle system [8].…”
Section: Introductionmentioning
confidence: 99%
“…A solid polymeric vesicle, namely palmitoyl glycol chitosan, was entrapped within a liposomal formulation to control the release profiles of a model compound [8]. A small degree of mixing of the lipids occurred upon hydration of the lipid/surfactant film, resulting in a vesicle formulation instead of a vesicle in vesicle system [8]. The results showed that the polymeric vesicle phospholipid in vesicle system released 28% of the entrapped model compound compared to 62% from the polymeric vesicles over the duration of 4 hours [8].…”
Section: Introductionmentioning
confidence: 99%